Crafting Success: Amplifying Public Speaking and Personal Branding for Kinabalu High School Students, Malaysia - Herlitah; Febrilia, Ika; Febriantina, Susan; Nindito, Marsellisa; Zulaihati, Sri; Dianta A, Karuniana; Nurmalasari, Dewi; Mundiharno (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
Public speaking is a critical component of strengthening personal branding, as it allows individuals to build credibility, connect authentically with their audience, and demonstrate their expertise. This article provides an overview of how public speaking and personal branding create success for high school students, along with effective strategies for leveraging these skills using descriptive analytical methods. The importance of public speaking in personal branding is highlighted, including its role in increasing visibility and credibility, enabling authentic connections, and positioning individuals as thought leaders. Strategies for effective public speaking are discussed, such as crafting a compelling narrative, knowing your audience, mastering non-verbal communication, leveraging technology and social media, and continuous improvement. Challenges in overcoming public speaking anxiety are discussed, with suggestions such as thorough preparation by mastering the material well, visualization techniques, and focusing on the value provided to the audience. The article concludes by emphasizing that mastering public speaking is a powerful tool for shaping and enhancing personal branding, and that by using effective strategies and continually refining skills, individuals can significantly enhance their professional identity and create lasting impressions that foster career growth.